Rationale for mental training of elite wrestlers - Rutkowska, K.; Gierczuk, D.; Bujak, Z. (Archives of Budo Conference Proceedings, 2015)
Background and Study Aim. Ways of coping with stress and emotional intelligence are significant psychological variables which co-determine good health and effective functioning in various situations. Defining the level of these variables and their correlations will make it possible to get to know the psychological profile of wrestlers and formulate guidelines for mental training. The aim of the research presented in this work was the knowledge about the level of two variables (their dimensions and correlations between them), i.e. emotional intelligence and styles of coping with stress. Material and Methods. The research included 40 Greco-Roman wrestlers aged 18-22 with training experience from 6 to 12 years. A questionnaire and two psychological examination methods, i.e. Coping Inventory for Stressful Situations (CISS) and Two-Dimensional Emotional Intelligence Inventory (DINEMO) were used in the research. An average level of the measured variables in wrestlers was noted. The distribution of proportions of the categories of low, average and high results as well as correlations between the variables suggested the necessity to undertake directed psychoeducational activities in the training process. Improving these characteristics will let wrestlers function more effectively in sports situations, especially in a sports fight, but also in non-sports situations, such as the period after they have retired from sport. Results. Relatively lowest results were obtained in the scale measuring emotion-oriented style (the result lower than in the SSZ scale - Z=-2.15, p=0.3 and lower than in the SSU scale - Z=-4.02, p=0.00). Every fifth wrestler represented a high level of results in GEN scale, including one person who got the highest result of a sten of 10. In turn, ca. ¾ of the examined group obtained average results. Within OTHERS scale 3 participants obtained high results (at the level of a sten of 8), while the majority (i.e. 8 out of 10 participants) obtained average results. Two wrestlers obtained low results within ME scale, while nearly 30% of the participants had high results. Conclusion. It is relevant to implement directed corrective, educational and prophylactic activities from the field of sports psychology into a training cycle. It is significant for wrestlers to be aware of the role of emotional intelligence and of the process of coping with stress. Equipping wrestlers with indispensable knowledge and mastering appropriate abilities will, in consequence, develop the desired competences. It will also improve the efficiency of functioning in sport as well as health and quality of life.